Gestation length and racing performance in 115 Thoroughbred foals with incomplete tarsal ossification. (20th July 2017) - Haywood, L.; Spike‐Pierce, D. L.; Barr, B.; Mathys, D.; Mollenkopf, D.
Summary: Background: Incomplete ossification of the cuboidal bones of the carpus and tarsus in foals has the potential for significant consequences including chronic lameness and decreased athletic ability. Objectives: To determine if the degree of ossification of the cuboidal bones is associated with gestational length and if the diagnosis of incomplete ossification is a predictor of performance in Thoroughbred racehorses. Study design: Retrospective cohort study. Methods: The medical records of Thoroughbred foals less than 90 days of age from 1994 to 2011 were examined and records containing tarsal radiographs identified. Radiographs of the tarsus were examined for signs of incomplete ossification and those that were incompletely ossified graded on a scale of 1–4 using a modification of a previously reported index, with Grade 1 being the least ossified and Grade 4 being the most. Gestational length was determined by examining breeding records and foaling dates reported to the Jockey Club. Race records for 2‐ and 3‐year‐old affected foals and their maternal siblings were obtained and compared. Results: Foals with Grades 1 and 2 ossification were usually premature (gestation length <325 days), but Grades 3 and 4 were not. Foals with Grades 2 and 3 ossification were significantly less likely to race than their maternal siblings and Grades 1, 2, 3 and 4 foals earned less money. Main limitations: A larger sample size of foals with Grade 1 ossification would increase the power of the study. Foals radiographed at an older age may have had lower ossification scores if radiographed earlier. Conclusions: Incomplete ossification, especially Grades 1 and 2, is associated with a short gestation length. Foals with Grades 2 and 3 incomplete ossification were less likely to race and Grades 1, 2 and 3 earned around $30, 000 less than their maternal siblings.